Can Visual Inspection after Acetic acid replace Papanicolaou smear. Issue 1 (February 2015) - Arya, Rakhi; Arora, Raksha; Benwal, Devendra; Kumar, Vijaya K.; Verma, Surendra
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to determine the sensitivity and specificity of acetic acid application to the cervix as a screening test for cervical cancer and to compare it with Papanicolaou smear and correlate it with histopathology of colposcopy-directed biopsy. Setting The study was conducted in a tertiary care centre. Design The study was conducted as a prospective trial. Materials and methods Papanicoloau smear was taken, and the cervix was visualized after application of 5% acetic acid. Women with positive Pap smears or positive naked eye acetic acid test (NEAT) were subjected to colposcopy and directed biopsies were obtained. Results The sensitivity of NEAT was higher than that of Pap smear (80.3 vs. 24.5%), and the specificity of Pap smear was higher than that of NEAT (95.3 vs. 21.2%). Conclusion NEAT may serve as an adjunct to routine Pap smear to pick up additional 50% of premalignant lesions. It is not capable of replacing Pap smear because of its low specificity. The high false-positive rate of the acetic acid test may be due to the large number of unhealthy cervices (57.6%).